Pelatihan Pemanfaatan Software Geogebra dalam Pembelajaran Matematika pada MGMP Matematika - Ahmat Wakit; Lilik Sulistyo; Khotibul Umam; Ariyanto Ariyanto; Decky Rochmanto (Faculty of Engineering, Universitas Semarang, 2024)
The Mathematics Subject Teacher Meeting (MGMP) at KKMA 02 Jepara is routinely held at least 3 times in a semester, namely at the beginning before learning begins, in the middle, and at the end of the semester. The routine activities carried out are discussing textbooks and worksheets, setting up learning traps, and preparing for the preparation of Mid-Semester Examination questions and Final Semester Examination questions. However, in the last few semesters, the Mathematics MGMP is rarely held, even in this semester there is only 1 meeting and there is no more meeting agenda. This is due to several factors such as the level of saturation because the activities carried out are the same, never innovative activities that are in nature to improve the abilities and skills of teachers such as training, this encourages community service programs to be held with the theme